The Effect of Leader Member Exchange, Job Satisfaction and Motivation on Educational Personnels’ Organizational Commitment of Jakarta Mercu Buana University - Saputra, Asep; Ariyanto, Eny (International Review of Management and Marketing, 2019)
This study aims to examine and analyze the effect of leader member exchange (LMX), job satisfaction and motivation on educational personnels’ organizational commitment of Jakarta Mercu Buana University. This research used causal analysis with quantitative approach. The population is all educational personnels of Jakarta Mercu Buana University. The sample collection technique used non-probability sampling with convenience sampling. The sample is 186 educational personnels obtained based on Yamane approach formula. Data analysis using multiple linear regression. The result showed that leader member exchange (LMX) has positive and significant effect on organizational commitment. Job satisfaction has positive and significant effect on organizational commitment. Motivation has positive and significant effect on organizational commitment. Leader member exchange (LMX), job satisfaction and motivation simultaneously are having significant effect on organizational commitment. Recommendations for Jakarta Mercu Buana University to maintain and enhance leader member exchange (LMX), job satisfaction and employee motivation in order to increase organizational commitment. Keywords: Leader Member Exchange (LMX), Job Satisfaction, Motivation and Organizational Commitment. JEL Classifications: D23, I23, M5, M54 DOI: https://doi.org/10.32479/irmm.8650